The Effect of Job Insecurity, Work Stress and Self Efficacy on the Performance of Employees of Pt. Bank Rakyat Indonesia Bajawa Branch Office, Flores Ntt - Fransiska Saferia Moi; Siti Mujanah (Sharia Oikonomia Law Journal, 2024)
This study aims to determine and analyze the effect of Job Insecurity, Work Stress, Self Efficacy on Employee Performance of PT. Bank Rakyat Indonesia Bajawa Branch Office, Flores NTT. This study used a quantitative approach. The respondents of this study were all employees of BRI Bajawa Branch as many as 44 respondents. The data analysis method used is multiple linear regression analysis. The t test and F test are used to test the hypothesis. The results showed that Job Insecurity negatively affects employee performance Work stress does not affect employee performance and Self Efficacy affects employee performance Test F results show that Job Insecurity, Work Stress and Self Efficacy simultaneously affect employee performance.